A food composition database for assessing nitrate intake from plant-based foods. (15th November 2022) - Zhong, Liezhou; Blekkenhorst, Lauren C.; Bondonno, Nicola P.; Sim, Marc; Woodman, Richard J.; Croft, Kevin D.; Lewis, Joshua R.; Hodgson, Jonathan M.; Bondonno, Catherine P.
Highlights: Nitrate food composition database for plant foods will enable dietary nitrate assessment. Up-to-date nitrate database covers main plant-based food groups. Nitrate content data for 264 plant-based foods from 64 countries. Leaf vegetables were the top nitrate-containing plant-based foods. Banana and strawberry contained higher amount of nitrate than previously acknowledged. Abstract: An up-to-date nitrate food composition database of plant-based foods is lacking. Such a resource is imperative to obtain a robust assessment of dietary nitrate intakes and facilitate more empirical evaluation of health implications. We updated and expanded our 2017 vegetable nitrate database by including data published between 2016 and 2021, and data on fruits, cereals, herbs, spices, pulses and nuts (1980 – 2021). Of the collated nitrate contents for 264 plant-based foods from 64 countries, 120 were obtained from three or more references. Despite substantial variations, leaf vegetables were the top nitrate-containing foods, followed by stem & shoot vegetables, herbs and spices, root vegetables, flower vegetables, tuber vegetables, nuts, fruit vegetables, legume/seed vegetables, fruits and cereals. Banana and strawberry contained far higher amounts of nitrate than previously recognised. In conjunction with the recent animal-based food nitrate & nitrite database, this database can now be used to evaluate dietary nitrate intake in clinical and epidemiological studies.